WHO study on Prevention of REcurrences of Myocardial Infarction and StrokE (WHO-PREMISE) - Shanthi Mendis; Dele Abegunde; Salim Yusuf; Shah Ebrahim; Gerry Shaper; Hassen Ghannem; Bakuti Shengelia (The World Health Organization, 2005)
OBJECTIVE: To determine the extent of secondary prevention of coronary heart disease (CHD) and cerebrovascular disease (CVD) in low- and middle-income countries. METHODS: A descriptive cross-sectional survey of a sample of 10 000 CHD (85.2%) and CVD (14.8%) patients (6252 men; 3748 women) was conducted over 6 months in geographically defined areas. The mean age was 59.2 years (standard deviation (SD), 10.8). Consecutive patients were recruited from a stratified random sample of primary, secondary and tertiary care facilities in defined areas in 10 countries (Brazil, Egypt, India, Indonesia, Islamic Republic of Iran, Pakistan, Russian Federation, Sri Lanka, Tunisia and Turkey). The main outcome measures were levels of lifestyle and physiological risk factors, and the use of drugs for secondary prevention of CHD and CVD. FINDINGS: Approximately 82%, 89% and 77% of patients were aware of the cardiovascular benefits of quitting smoking, a heart-healthy diet and regular physical activity, respectively. About half (52.5%) engaged in less than 30 minutes of physical activity per day, 35% did not follow a heart-healthy diet and 12.5 % were current tobacco users. Blood pressure had been measured in 93.8% (range 71-100%), blood cholesterol in 85.5% (range 29-97%) and blood sugar in 75.5% (range 65-99%) in the preceding 12 months. The proportions who had received medications among CHD and CVD patients were: aspirin, 81.2%, 70.6%; beta-blockers, 48.1%, 22.8%; angiotensin-converting enzyme inhibitor, 39.8%, 37.8%; statins, 29.8%, 14.1%, respectively. About one-fifth of patients with CHD had undergone revascularization. CONCLUSION: A significant proportion of patients did not receive appropriate medications. About 47% of patients had at least two or more modifiable risk factors (smoking, physical inactivity, hypertension, diabetes or hypercholesterolaemia). There are considerable missed opportunities for prevention of recurrences in those with established CVD in low- and middle-income countries.